How do you evaluate (2x + 3) ( 4- x )?

2 Answers
Oct 19, 2017

-2x^2 + 5x + 12

Explanation:

(2x+3) (4-x) = (2x+3)*4 + (2x+3)(-x)
= 8x + 12 -2x^2 -3x = 12 +5x - 2x^2

Oct 19, 2017

-2x^2+5x+12

Explanation:

To multiply two binomials, you want to use FOIL (which I'll explain a bit later). The idea is to multiply each term of one binomial with every term in the other binomial.

FOIL stands for First, Outer, Inner, Last.

First: Multiply the first term of each binomial.
(2x)*(4)=8x

Outer: Multiply the outer terms.
(2x)*(-x)=-2x^2

Inner: Multiply the inner terms.
(3)*(4)=12

Last: Multiply the last term of each binomial.
(3)*(-x)=-3x

Now, add everything you've got.

(8x)+(-2x^2)+(12)+(-3x)

Finally, simplify.

-2x^2+5x+12